Peningkatan Kualitas Semangat Dakwah dan Pengamalan Ilmu Melalui Kegiatan FITRAH (Fokus Tahsin dan Tadabbur Al-Fatihah) - Al-Fudiah, Nurul; Saputra, Adha; Azzahra, Aulia; Wijaya, Atta Salma; Ahsan, Najwa Luthfiana Zul; Aziz, Alimah Binti Abdul; Hajar, Hajar (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2025)
The knowledge acquired in academic fields should not only be used for personal benefit but also applied in everyday life, including through teaching the community. As female students in the field of Quranic Studies and Tafsir, it is essential to teach the correct recitation of the Quran to society from various backgrounds. Moreover, the need for proper Quranic recitation education has become increasingly urgent in today’s society. Dawah through Quranic teaching is crucial to improving religious understanding and practice. If female students are reluctant to engage with the community, the cycle of ignorance regarding the correct way to recite the Quran will continue and could negatively impact future generations. Many people still rely on inherited knowledge without proper understanding, while many female students with a background in Quranic education have yet to actively engage in teaching this knowledge.